Sustainability in Aquaculture - A Study in West Godavari District of Andhra Pradesh, India - Betala, Ajay Babu (Digital Repository of Theses, 2025)
Aquaculture has emerged as a significant contributor to food security, employment, and economic growth in India. West Godavari district of Andhra Pradesh is one of the leading regions for aquaculture production, particularly shrimp and freshwater fish farming. However, the rapid expansion of aquaculture has raised concerns about sustainability due to environmental degradation, resource depletion, and socio-economic challenges. This study examines the sustainability of aquaculture practices in West Godavari, focusing on environmental, economic, and social dimensions. The research employs a mixed-method approach, combining primary data collection through surveys and interviews with secondary data analysis from government and industry reports. Key indicators of sustainability, such as water quality management, feed efficiency, government policies, and regulatory compliance, are analyzed. The study also evaluates the impact of intensive aquaculture on local ecosystems. Findings indicate that while aquaculture has significantly improved rural livelihoods and contributed to export earnings, challenges such as excessive antibiotic use, pollution from feed waste, and declining biodiversity pose threats to long-term sustainability. The study explores best management practices (BMPs) and policy interventions that can promote environmentally responsible and economically viable aquaculture. Recommendations include adopting eco-friendly technologies, improving farmer awareness, and strengthening regulatory frameworks to ensure a balance between productivity and ecological conservation. This research provides valuable insights for policymakers, farmers, and industry stakeholders to enhance the sustainability of aquaculture in West Godavari. By addressing the existing challenges, sustainable aquaculture can continue to thrive while minimizing its environmental footprint and ensuring long-term economic benefits for the region.